Effects of Government Policy on the Nexus between Project Management Practices and Sustainability of Agribusiness Projects in Kenya - Miano, Kabethi Joseph; Ngugi , Lucy; Maingi , James (African Journal of Education,Science and Technology (AJEST), 2024)
The study sought to establish the effects of government policy on the relationship between known project management practices and sustainability of Kenya Agricultural Productivity and Agribusiness Projects(KAPAP) in selected Counties in Kenya. The predictor variables were capacity building practices, stakeholder management practices, project design practices, and monitoring and evaluation practices, while project sustainability was the response variable. Descriptive and explanatory designs were utilized both in the study. The population comprised of 6,401 KAPAP projects implemented between years 2012 to 2015. A sample of 376 respondents was selected through multistage random sampling methods. A semi-structured questionnaire whose reliability was tested through Cronbach alpha coefficient at 0.7 threshold was used for data collection. Multiple linear regression models were applied in data analysis after testing for normality, linearity and multicollinearity. From the findings, each of the four project management practices had a statistically significant influence on the sustainability of KAPAP projects. There was 71.8% joint influence of independent variables on the dependent variable. The proportion of joint explanation improved by 6.9% on inclusion of government policy as a moderating variable. This confirmed that government policy statistically and significantly moderated the relationship between project management practices and project sustainability. The study recommends that project management practices should be closely integrated with government policies to significantly enhance the sustainability of projects, particularly in the agribusiness sector. In addition, project managers and other stakeholders should proactively align their project strategies with current and emerging government policies to enhance sustainability. It is also recommended that policymakers should work collaboratively with project management teams to develop and nature a supportive policy environment for projects. The collaborative approach would lead to development of policies that are both practical and beneficial, ultimately contributing to the achievement of sustainable project objectives.